Degradation of Organic Matter Using A Submerged Micro Bubble Diffuser in Biological Wastewater Treatment System - Kutty S.R.M., Kutty (WIT, 2010)
In most biological wastewater treatment systems, aeration is provided using millimeter diffusers of various sizes. The aeration is to provide mixing as well as oxygen for the microorganisms in the degradation of organic matter. In this study, the effectiveness of using micro diffusers in the degradation of organic matter was evaluated. Two reactors A and B, of size 140x140x500 mm were constructed using perspex to treat municipal wastewater. Aeration in the reactors A and B was provided using millimeter diffuser and micro diffuser, respectively. The diffusers consist of perforated aluminium plate to generate millimeter bubbles and sintered porous glass to generate micro bubbles. Compressed air was forced through two parallel flow meters at flow rate of 2.5 L/min. Biomass for both reactors were acclimatized prior to treating the municipal wastewater in the reactors. Two batch experiments were conducted at 26°C for the estimation of the kinetic parameters for the degradation of organic matter. Samples were evaluated for chemical oxygen demand (COD) and soluble chemical oxygen demand (sCOD) for both reactors at at approximately 1 hour, 3 hours, and every 6 hours respectively, until 48 hours, for each batch of experiment. From the results of the study, it was found for the micro and millimeter diffusers, the degradation kinetic parameter kCOD was found to be 0.041 and 0.028, repectively for COD and ksCOD to be 0.060 and 0.044, respectively for sCOD. On average, micro and millimeters diffusers removed COD at approximately 87% and 81%, respectively, and removed sCOD at approximately 91% and 75%, respectively. It can be concluded that the use of micro diffuser can provide higher degradation of organic matter. Keywords: Micro air bubbles, COD, sCOD, DO, kinetics evaluation